Hubungan tingkat aktivitas fisik dengan status gizi mahasiswa Fakultas Kedokteran Unand pada pandemi COVID-19 - Afi Putra Perdana Nurullah; Desmawati Desmawati; Abdiana Abdiana; Rauza Sukma Rita; Fathiyyatul Khaira; Elmatris Elmatris (Majalah Kedokteran Andalas, 2023)
Objective: To determine the relationship between levels of physical activity and the nutritional status of the year 2019 undergraduate medical students at Andalas University during the COVID-19 pandemic; Method: This study was a quantitative study using a cross-sectional method with 151 respondents held in September 2022 at Medical Faculty Andalas University. The study used an IPAQ-short form questionnaire to ensure the levels of physical activities and direct anthropometry to measure the nutritional status. Analysis between the physical activity data and the nutritional status data was tested using the Pearson chi-square test; Result: The result of the study showed that 42,4% of respondents have low physical activity, 44,4% of respondents have normal nutritional status, the chi-square test between physical activity and nutritional status of was p=0,349; Conclusion: there was no significant relationship between levels of physical activity and the nutritional status of undergraduate medical students at Andalas University during the COVID-19 pandemic. It is suggested that improving physical activity amongst undergraduate students is highly encouraged as it prevents non-communicable diseases.